A survey of the professional status and training needs of private academic librarians in the Philippines - Eriman, Bebien F. (2002)
This descriptive study determined the professional status and training needs of private academic librarians in the Philippines. It used a structured questionnaire to gather data from 129 respondents selected through stratified random sampling. This figure represented 60 of the 129 private academic libraries in the country. The results show that private academic librarians in the Philippines are mostly females, between 31-40 years of age, mostly graduates of education and related fields, hold different position/titles, are predominantly college librarians, perform duties and responsibilities according to their job description, are both licensed and unlicensed, and skilled in library management and supervision. The seminar-workshops and training programs attended for the last five years are perceived by most respondents as very relevant. The majority of the respondents indicated that computer literacy and information technology are the training needs of librarians in the next five years.